Principal’s Role in Addressing Issues Affecting Teacher Competence to Improve Teaching and Learning Processes at SMA Negeri 1 Tanjung Pura - Damayanti, Mita; Damanik, Rabukit; D, Hamidah. (Pusdikra Publishing, 2025)
This study aims to analyze the role of the principal in improving teachers’ competence at SMA Negeri 1 Tanjung Pura. Teacher competence is a key factor in determining the quality of learning; therefore, the principal has a strategic responsibility in developing the professional abilities of educators. This research employs a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation, and then analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results show that the principal plays a crucial role in three main aspects: as a manager, a supervisor, and a motivator. As a manager, the principal organizes and implements teacher competence improvement programs through training, workshops, and continuous professional development activities. As a supervisor, the principal conducts planned academic supervision to monitor and evaluate teacher performance. Meanwhile, as a motivator, the principal provides encouragement, recognition, and creates a conducive work climate to enhance teachers’ enthusiasm and performance. In addition, the principal also plays a role in addressing current challenges, such as the low mastery of learning technology, by organizing ICT training and encouraging teacher collaboration to share experiences and teaching innovations. The findings of this study affirm that the success of improving teacher competence is greatly influenced by effective, participative, and professionally development-oriented school leadership.